Biomechanical evaluation of four surgical techniques for ventral stabilization of the atlantoaxial joint in dogs - Ferreira, Danyelle Rayssa Cintra [UNESP]; Dias, Luís Gustavo Gosuen Gonçalves [UNESP]; Minto, Bruno Watanabe [UNESP]; Rocha, Thiago André Salvitti de Sá; Malta, Caio Afonso Dos Santos [UNESP]; Conceição, Maria Eduarda Bastos Andrade Moutinho da [UNESP]; Lucena, Dayvid Vianêis Farias de [UNESP] (FapUNIFESP (SciELO), 2023)
Purpose: This study compared, through biomechanical evaluation under ventral flexion load, four surgical techniques for ventral stabilization of the atlantoaxial joint in dogs. Methods: In total, 28 identical atlantoaxial joint models were created by digital printing from computed tomography images of a dog, and the specimens were divided into four groups of seven. In each group, a different technique for ventral stabilization of the atlantoaxial joint was performed: transarticular lag screws, polyaxial screws, multiple screws and bone cement (polymethylmethacrylate–PMMA), and atlantoaxial plate. After the stabilization technique, biomechanical evaluation was performed under ventral flexion load, both with a predefined constant load and with a gradually increasing load until stabilization failure. Results: All specimens, regardless of stabilization technique, were able to support the predefined load without failing. However, the PMMA method provided significant more rigidity (p ≤ 0.05) and also best resisted the gradual increase in load, supporting a significantly higher maximum force (p ≤ 0.05). There was no statistical difference in flexural strength between the transarticular lag screws and plate groups. The polyaxial screws method was significantly less resistant to loading (p ≤ 0.05) than the other groups. Conclusion: The PMMA technique had biomechanical advantages in ventral atlantoaxial stabilization over the other evaluated methods.
Keywords: Atlanto-Axial Joint; Axis, Cervical Vertebra; Cervical Atlas; Dogs; Odontoid Process; Printing, Three-Dimensional